2015
DOI: 10.1111/ajo.12397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anterior vaginal mesh with concomitant mid‐urethral sling surgery on stress urinary incontinence: clinical and sonographic outcome

Abstract: Among women who had MUS, there were no differences in the ultrasound and clinical outcome between those who had AVM or otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
2
Order By: Relevance
“…Most published studies show equal efficacy of TOT used as a single procedure or combined with prolapse surgery [18][19][20][21]. Only the results of 2 studies revealed a better outcome for sling performed concomitantly with prolapse surgery [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies show equal efficacy of TOT used as a single procedure or combined with prolapse surgery [18][19][20][21]. Only the results of 2 studies revealed a better outcome for sling performed concomitantly with prolapse surgery [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, poor bladder mobility after transvaginal mesh surgery may explain the lesser compressive effect of the sling during the Valsalva maneuver. Lo et al [20] reported that the mobility of the mesh and/or bladder neck had an important role in determining the success rate of middle urethral sling surgery in sonography findings. In the current study, the lesser compressive effect was reflected in the short axis of the proximal urethra in the sling and mesh group.…”
Section: Discussionmentioning
confidence: 99%
“…A hálóműtétek relatíve alacsony kiújulás mellett (2-4,8%) [8,14] viszonylag magas szövődményrátával bírtak. Így a háló eróziója, mint a leggyakoribb és a betegek számára a legtöbb szenvedést okozó eltérés, 3,8-43,6% között [8,14,[16][17][18][19], visszatérő húgyúti infekciók az esetek 2,9%ában [20], de novo urge incontinentia (DNUS) 8,7-17%ban [8,20] fordult elő. Dyspareunia hüvelyi hálóműtéteket követően az esetek 28,6%-ában lépett fel, ugyanakkor érdekes tény, hogy a hüvelyi és a has felől behelyezett hálók között szignifikáns eltérés e téren nem volt megfigyelhető [21,22].…”
Section: A Hálóműtétek Szövődményeiunclassified
“…Ebben a csoportban a legsúlyosabb szövődményt, a háló kilökődését a betegek 8,3%-ánál tapasztaltuk. Az általunk észlelt kilökődés (8,3%) és DNUS-előfordulás (11,9%) a nemzetközi irodalommal (3,8-43,6% és 8,7-17%) teljesen megegyezik [8,14,[16][17][18]20].…”
Section: Megbeszélésunclassified